Quality Control and Standardization of Rabeprazole Tablets: Quality Control and Standardization of Rabeprazole Tablets - Chuvashova, Dinara; Anisimov, Alexander; Garmonov, Sergey; Egorova, Svetlana (Iranian Journal of Pharmaceutical Sciences, 2020)
Rabeprazole sodium is a new stable pharmaceutical composition developed by us in tablet form, consisting of rabeprazole sodium as active ingredient, excipients, a separating layer and enteric coating. The manufacturing method involves pressing with preliminary wet granulation. In this work, a method was developed for the quantitative determination of rabeprazole sodium in tablets with simultaneous determination of impurities, using high-performance liquid chromatography with diode-array detection. Chromatographic conditions were established for the separation of rabeprazole and impurities on С18 sorbent, using mobile phase: 0.05% К2НР04, 0.27% КН2Р04 with pH 6.8; and acetonitrile in ratio of 70:30 (v/v), using isocratic elution mode. Furthermore, a method was developed for the spectrophotometric determination of rabeprazole sodium and the conditions of its release during dissolution test were optimized. The feasibility of the developed techniques for the analysis of enteric coated rabeprazole tablets was evaluated with the following parameters: specificity, accuracy, stability of solutions, linearity, convergence, and reproducibility. The techniques were confirmed suitable for the determination of impurities in the drug and for its quantitative analysis.